Findings from a pilot randomised trial of a social network self-management intervention in COPD - Lindsay Welch (BMC Pulmonary Medicine, 2020)
Abstract Background Self-Management Support (SMS), refers to the actions taken by individuals to recognise and manage their own health. It is increasingly recognised that individuals with chronic obstructive pulmonary disease (COPD) require additional support with their Self-management. Emerging evidence suggests that the use of a social network intervention can improve health outcomes and increase quality of life. In order to understand the potential benefits of SMS in COPD, the GENIE (Generating Engagement in Network Support) SMS tool was implemented and evaluated in a COPD primary care context. The GENIE intervention is a social networking tool that consists of 3 parts; a concentric circle modelling to map existing social networks; a questions sections to elicit preferences for activities; a map of selected resources is then produced, aligned with the user’s interests and suggestions for connections to existing network members and to new resources. Methods A pilot, parallel, single blind, block randomised controlled trial. Patients with COPD ranging from mild-very severe were recruited. Participants provided written consent and were then randomised to either the intervention or usual care. The primary aim was to understand the clinical benefit through the analysis of health status, symptom burden and quality of life. The secondary outcome measure was health utilisation. NHS cost differences were reported between groups using the GENIE intervention over usual care. Results The GENIE pilot results demonstrate maintenance in health status and clinical symptoms with a decrease in anxiety. An overall increase in quality of life was observed, these findings did not reach significance. A cost reduction was demonstrated in inpatient stay with no difference in primary care costs. Overall a cost reduction in NHS service utilisation was indicated in the intervention group. Conclusion This pilot study indicated that using a social network intervention can encourage the development of new social connections and extend existing support networks for COPD patients. Increasing network support in this population is of benefit to both patients and NHS providers in terms of cost reductions and enhancing wellbeing. This broadens the understanding of possible new approaches to SMS in community COPD patients, which could now be investigated in a larger population over a longer period. Trial registration Clinical Trials.gov PRS National Library of Medicine. Protocol ID number: 19175, Clinical Trial ID: NCT02935452 .